Project management : a multi-perspective leadership framework - Mikkelsen, Hans; Riis, Jens Ove (Emerald Publishing, 2017)
Modern projects are confronted with complexity and ambiguity. To provide a holistic framework, this book presents a new project management model that is used to identify the nature of a project and develop appropriate project solutions. It also allows a circular planning process, leading to coherence across the project's elements.
Keywords: Project management.; elektronické knihy; electronic books